Chemokine CX3CL1 and its receptor CX3CR1 are associated with human atherosclerotic lesion volnerability. Issue 6 (June 2015) - Zhang, Xiaolin; Feng, Xueyao; Cai, Wenzhi; Liu, Tengfei; Liang, Zhenyang; Sun, Ying; Yan, Chenghui; Han, Yaling
Abstract: Background: CX3CL1 and its receptor CX3CR1 have been emphasized in atherosclerosis recently. In this study we investigated the role of the chemokines CX3CL1 and their receptor CX3CR1 in atherogenesis and identified whether the genetic variations in CX3CL1 and CX3CR1 impacted the atherosclerosis process in coronary artery disease (CAD) or not. Methods: CX3CL1/CX3CR1 expression in coronary and carotid artery specimens were analysed by immunohistochemistry. CX3CR1 expression on CD4 + CD28 - T cells was analysed by flow cytometry. We also screened for CX3CL1/CX3CR1 sequence variations selected from the hapmap database and examined the association between CX3CL1/CX3CR1 and CAD in the Chinese Han population. Results: Immunohistochemical staining of tissue from CAD patients showed increased CX3CL1/CX3CR1 expression in atherosclerotic coronary and carotid artery plaques compared with normal arteries. CX3CL1/CX3CR1 expression was correlated with the severity of the atherosclerosis lesion. Patients with CAD also showed an increased number of CX3CR1 + CD4 + CD28 - T cells. Compared with their corresponding wild-type genotypes, CX3CL1 rs170364 and CX3CR1 rs17793056 were associated with increased susceptibility to CAD. Conclusions: CX3CL1 and CX3CR1 may contribute to the formation of coronary atherosclerotic plaque in CAD.CX3CL1 rs170364 and CX3CR1 rs17793056 polymorphisms may be independent genetic risk factors for CAD. Highlights: CX3CL1 and CX3CR1 may contribute to the formation of atherosclerotic plaque in CAD. CX3CL1 and CX3CR1 variants may be independent genetic risk factors for CAD. CX3CL1 and CX3CR1 expression may be a risk factor for atherosclerosis. Reducing CX3CL1 levels may represent a novel therapeutic strategy for CAD.